Bone morphogenetic protein‐5, a key molecule that mediates differentiation in MC3T3E1 osteoblast cell line. (12th May 2017) - Vijayan, Viji; Gupta, Sakshi; Gupta, Sarika
Abstract: Bone morphogenetic protein‐5 (BMP‐5) is a member of the TGF receptor‐β family with osteoinductive property. However, its physiological role in osteoblast differentiation is not defined. This study highlights the importance of BMP‐5 in MC3T3E1 osteoblast differentiation. Pre‐osteoblasts exposed to osteogenic media (ascorbic acid, 50 µg/ml and β‐glycerophosphate, 10 mM) showed high protein expression of BMP‐5 in cell lysates and cell culture supernatants, which peaked during early time‐points of differentiation and declined with onset of mineralization. Attenuation of endogenous BMP‐5 protein expression by RNA interference downregulated the expression of type I collagen (COLIA1), an early osteoblast differentiation marker but not osteocalcin, a late osteoblast differentiation marker. Further experiments to analyze the cell signaling components revealed that BMP‐5 modulates COLIA1 expression via p38‐Runx2 axis involving Runx2 (Ser19) phosphorylation. These effects were also observed when recombinant BMP‐5 was added to pre‐osteoblast cultures reinforcing the fact that BMP‐5 is a modulator of COLIA1 expression. We conclude that BMP‐5 has stage‐specific role to play during MC3T3E1 osteoblast differentiation in part by autocrine p38/Runx2/COLIA1 signaling. © 2017 BioFactors, 43(4):558–566, 2017